Original paperA comparative analysis of advanced techniques for skin reconstruction with autologous keratinocyte culture in severely burned children: own experience - Chrapusta, Anna; Nessler, Michał B.; Drukala, Justyna; Bartoszewicz, Marzenna; Mądry, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: The local treatment in burns larger than 50% of total body surface area is still the great challenge for surgeons. Aim: This paper presents a review of different solutions for deep burn wound healing in children and the early outcomes of treatment with combined autologous cell culture technique. Material and methods: For this study, 20 children aged between 4 and 12 years with 55–65% of TBSA III grade burn injury were analyzed. A skin sample, 1 cm × 1 cm in size, for keratinocyte cultivation, was taken on the day of the burn. After necrotic tissue excision, the covering of the burned area with an isolated meshed skin graft was carried out between day 4 and 7. After 7 days of keratinocyte cultivation, the mentioned areas were covered with cells from the culture. We divided the burned regions, according to the way of wound closure, into 3 groups each consisting of 15 treated regions of the body. We used meshed split thickness skin grafts (SSG group), cultured autologous keratinocytes (CAC group), and both techniques applied in one stage (SSG + CAC group). Results : In the SSG group, the mean time for complete closure of wounds was 12.7 days. Wounds treated with CAC only needed a non-significantly longer time to heal – 14.2 days (p = 0.056) when compared to SSG. The shortest time to heal was observed in the group treated with SSG + CAC – 8.5 days, and it was significantly shorter when compared to the SSG and CAC groups (p < 0.001). Conclusions : This study suggests that cultured keratinocytes obtained after short-time multiplication, combined with meshed autologous split thickness skin grafts, constitute the optimal wound closure in burned children.